Application of Behavioristic Learning Theory of Creative Mathematics Learning in Increasing Student Learning Motivation - Ena Juliatni, Ni Kadek; Suarni, Ni Ketut; Margunayasa, I Gede (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to analyze the effectiveness of the application of behavioristic learning theory in creative mathematics learning in increasing student learning motivation. This study uses a qualitative approach with a descriptive method, where data is collected through observation, interviews, and documentation to gain an in-depth understanding of the experiences of students and teachers in applying this method. The subjects in this study are 26 students in grade V of SD Negeri 3 Ubung, as well as informants consisting of class teachers and school principals. The data analysis technique uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing to identify the main patterns that appear related to student learning motivation. The results of the study show that the application of behavioristic theory in creative mathematics learning has a positive impact on students' learning motivation. Most students showed an increase in the courage to ask questions, active participation in class, and confidence in working on math problems. In addition, the use of positive reinforcement such as achievement stars, praise from teachers, and interactive teaching aids has been proven to increase students' interest in mathematics. The application of this method also helps to change the perception of students who previously considered mathematics as a difficult and scary subject to be more interesting and fun. The conclusion of this study is that the application of behavioristic theory in creative mathematics learning can significantly increase students' learning motivation and create a more conducive learning environment. The implications of this study show that teachers need to apply positive reinforcement strategies more broadly in learning, especially in subjects that are considered difficult by students, and consider the use of interactive tools to increase student involvement in the teaching and learning process. Therefore, this method can be used as one of the effective approaches in increasing the effectiveness of mathematics learning in elementary schools. Penelitian ini bertujuan untuk menganalisis efektivitas penerapan teori belajar behavioristik dalam pembelajaran matematika kreatif dalam meningkatkan motivasi belajar siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, di mana data dikumpulkan melalui observasi, wawancara, dan dokumentasi untuk memperoleh pemahaman mendalam tentang pengalaman siswa dan guru dalam menerapkan metode ini. Subjek dalam penelitian ini adalah siswa kelas V SD Negeri 3 Ubung yang berjumlah 26 orang, serta informan yang terdiri dari guru kelas dan kepala sekolah. Teknik analisa data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan untuk mengidentifikasi pola-pola utama yang muncul terkait motivasi belajar siswa. Hasil penelitian menunjukkan bahwa penerapan teori behavioristik dalam pembelajaran matematika kreatif berdampak positif terhadap motivasi belajar siswa. Sebagian besar siswa menunjukkan peningkatan dalam keberanian bertanya, partisipasi aktif dalam kelas, serta kepercayaan diri dalam mengerjakan soal matematika. Selain itu, penggunaan reinforcement positif seperti bintang prestasi, pujian dari guru, dan alat peraga interaktif terbukti dapat meningkatkan minat siswa terhadap matematika. Penerapan metode ini juga membantu mengubah persepsi siswa yang sebelumnya menganggap matematika sebagai mata pelajaran yang sulit dan menakutkan menjadi lebih menarik dan menyenangkan. Kesimpulan dari penelitian ini adalah bahwa penerapan teori behavioristik dalam pembelajaran matematika kreatif dapat secara signifikan meningkatkan motivasi belajar siswa dan menciptakan lingkungan pembelajaran yang lebih kondusif. Implikasi dari penelitian ini menunjukkan bahwa guru perlu menerapkan strategi penguatan positif secara lebih luas dalam pembelajaran, terutama dalam mata pelajaran yang dianggap sulit oleh siswa, serta mempertimbangkan penggunaan alat bantu interaktif untuk meningkatkan keterlibatan siswa dalam proses belajar mengajar. Oleh karena itu, metode ini dapat dijadikan sebagai salah satu pendekatan yang efektif dalam meningkatkan efektivitas pembelajaran matematika di sekolah dasar.